(untitled) (Environmental Smoke, 2019)
The purpose of this study is to address traumas in the oral cavity due to the use of removable or total prostheses, that either fit poorly into the oral cavity or are incorrectly sanitized by the patient. We highlight the need for a Surgical Dentist to perform possible corrections, and to perform a follow-up of the patient after the procedure. It is noteworthy that lesions such as ulcers and gum overgrowths can be avoided satisfactorily if the dental surgeon is able to perform an adequate treatment after the installation. A dental surgeon should be qualified to establish the real need for correction. His close interaction with the patient is the main point for the success of the work.